Revised Seventh Five Year Plan 1985-90 Vol. III Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1985)
The Lakshadweep has got a land use area of 28.3 Kms. for a population of 40239. Thus per capita availability of land is only 0.6 hectors. Even this small area is prone to heavy sea erosion. During the VI th Plan period a sum of ks.60.00 lakhs was agreed to protect the land and properties from sea erosion. Until 1982, about 1300 metres of shore were covered by protection works done through the Lakshadweep harbour Works but this was found to be very costly and was stopped in 1983. the expenditure incurred in the 6th Plan was Rs. 47 lakhs.
Planning Department Secretariat Union Territory of Lakshadweep